Inhaled amikacin for severe Gram-negative pulmonary infections in the intensive care unit: current status and future prospects - Antoni Torres; Anna Motos; Denise Battaglini; Gianluigi Li Bassi (Critical Care, 2018)
Abstract Recently, the use of nebulized antibiotics in the intensive care unit, in particular amikacin, has been the subject of much discussion, owing to unconvincing results from the latest randomized clinical trials. Here, we examine and reappraise the evidence in favor and against this therapeutic strategy; we then discuss the potential factors that might have played a role in the negative findings of recent clinical trials. Also, we call attention to several factors that are seldom considered by study developers and regulatory agencies, to promote translational research in this field and improve the design of future randomized clinical trials.